Information economy business strategies for competing in the digital age - Turner, Colin (London Kogan Page, 2000)
Information Economy is a study of how new technology {the internet telecommunication and IT}has changed the face of commerce. The author gives a clear view of this new and ever changing landscape.It gives detaited analysis of how to understand and recogni
Keywords: Information policy; Computer